First of all, I am not from English-using country so excuse my short english skill. This is the question from Halliday. I have solved this problem and checked the answer from my reference which started its statement with below F + Fn − (m + M)g = (m + M)a where m = 0.250 kg is the mass of the cheese, M = 900 kg is the mass of the elevator cab, F is the force from the cable, and 3.00 N, Fn = is the normal force on the cheese. And I think this explanation is wrong Shouldn't it be F - (m+M)g = (m+M)a ? Cuz what I think is for elevator) F-Mg-Fn=Ma (i) for cheese ) Fn-mg=ma (ii) (i)+(ii) -> F - (m+M)g = (m+M)a If I am wrong, please tell me what is my error.